Depolarizing GABA Transmission Restrains Activity-Dependent Glutamatergic Synapse Formation in the Developing Hippocampal Circuit - Salmon, Christopher K. (Front Cell Neurosci, 2020)
γ-Aminobutyric acid (GABA) is the main inhibitory neurotransmitter in the mature brain but has the paradoxical property of depolarizing neurons during early development. Depolarization provided by GABA(A) transmission during this early phase regulates neural stem cell proliferation, neural migration, neurite outgrowth, synapse formation, and circuit refinement, making GABA a key factor in neural circuit development. Importantly, depending on the context, depolarizing GABA(A) transmission can either drive neural activity or inhibit it through shunting inhibition. The varying roles of depolarizing GABA(A) transmission during development, and its ability to both drive and inhibit neural activity, makes it a difficult developmental cue to study. This is particularly true in the later stages of development when the majority of synapses form and GABA(A) transmission switches from depolarizing to hyperpolarizing. Here, we addressed the importance of depolarizing but inhibitory (or shunting) GABA(A) transmission in glutamatergic synapse formation in hippocampal CA1 pyramidal neurons. We first showed that the developmental depolarizing-to-hyperpolarizing switch in GABA(A) transmission is recapitulated in organotypic hippocampal slice cultures. Based on the expression profile of K(+)−Cl(−) co-transporter 2 (KCC2) and changes in the GABA reversal potential, we pinpointed the timing of the switch from depolarizing to hyperpolarizing GABA(A) transmission in CA1 neurons. We found that blocking depolarizing but shunting GABA(A) transmission increased excitatory synapse number and strength, indicating that depolarizing GABA(A) transmission can restrain glutamatergic synapse formation. The increase in glutamatergic synapses was activity-dependent but independent of BDNF signaling. Importantly, the elevated number of synapses was stable for more than a week after GABA(A) inhibitors were washed out. Together these findings point to the ability of immature GABAergic transmission to restrain glutamatergic synapse formation and suggest an unexpected role for depolarizing GABA(A) transmission in shaping excitatory connectivity during neural circuit development.